(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents the results of the study of the physical and chemical properties of raw shilajit collected in the Tien Shan mountains. According to the results of the study, it was proved that raw shilajit has substances of organic and inorganic origin in its structure. Organic substances are represented by compounds of an acidic nature of humic nature (humic and himatomelanic acids), organic acids (oxalic, benzenecarboxylic acids, methoxy acids, etc.), carbohydrates, amino acids. Minerals contain mainly compounds of magnesium, calcium, potassium, sodium and silicon. Trace amounts contain compounds of iron, aluminum, and some rare earth elements. The study of the physical and chemical properties of shilajit is an indicator of its quality, and according to them, it is possible to further determine the boundaries of the use of shilajit for therapeutic purposes.